On the nature of pre-freeze mortality in insects: water balance, ion homeostasis and energy charge in the adults of Pyrrhocoris apterus - Kostál, V; Vambera, J; Bastl, J (The Journal of experimental biology, 2004)
Three acclimation groups [i.e. non-diapause (LD), diapause (SD) and diapause, cold-acclimated (SDA)] of the adult bugs Pyrrhocoris apterus differed markedly in their levels of chill tolerance. Survival time at a sub-zero, but non-freezing, temperature of -5 degrees C (Lt50) extended from 7.6 days, through 35.6 days, to >60 days in the LD, SD and SDA insects, respectively. The time necessary for recovery after chill-coma increased linearly with the increasing time of exposure to -5 degrees C, and the steepness of the slope of linear regression decreased in the order LD>SD>SDA. The capacity to prevent/counteract leakage of Na(+) down the electrochemical gradient (from haemolymph to tissues) during the exposure to -5 degrees C increased in the order LD<SD<SDA. As a result, the rates of counteractive outward movement of K(+), and of the E(K) dissipation, decreased in the same order. The least chill-tolerant insects (LD) showed the highest rate of body-water loss. Most of the water was lost from the haemolymph compartment. The ability to regulate a certain fraction of ion pools into the hindgut fluid was the highest in the SDA group, medium in the SD group and missing in the LD group. The adenylate energy charge in the fat body cells was constant in all three groups. The total pools of ATP, ADP and AMP, however, decreased in the SD and SDA groups but remained constant in the LD group. The inability of insects to maintain ion gradients at sub-zero temperature is discussed as an important cause of pre-freeze mortality.
Keywords: aklimatizace; Sodium; draslík; analýza přežití; Potassium; Spectrophotometry; Fat Body; nízká teplota; Acclimatization; tukové těleso; zvířata; Adenine Nucleotides; Survival Analysis; Cold Temperature; adeninnukleotidy; osmolární koncentrace; časové faktory; Regression Analysis; Energy Metabolism; Body Water; tělesná voda; energetický metabolismus; sodík; Czech Republic; Heteroptera; spektrofotometrie; Animals; Česká republika; Time Factors; Osmolar Concentration; regresní analýza